Phenazopyridine associated acute interstitial nephritis and review of literature. (June 2014) - Singh, Manisha; Shailesh, Fnu; Tiwari, Upasana; Sharma, Shree G.; Malik, Bilal
Abstract Phenazopyridine is a urinary analgesic; commonly seen side-effects of this drug include, orange discoloration of urine, methemoglobinemia, yellowish skin discoloration, hepatitis and acute renal failure. Various case reports with phenazopyridine associated acute renal failure secondary to acute tubular necrosis have been reported in the literature. Acute kidney injury in these patients is caused by either direct injury to renal tubular epithelial cells or secondary to pigment induced nephropathy from hemolytic anemia. Hypoxic injury from phenazopyridine-induced methemoglobinemia has been well documented. We report a case of biopsy proven acute interstitial nephritis, associated with therapeutic doses of phenazopyridine without any evidence of methemoglobinemia or other mechanism of renal injury. Clinicians should be aware of the toxicity of this commonly used drug and should look closely for signs of renal insufficiency. Identifying and stopping the offending medication stays as the first step, but recent studies indicate that early steroid administration improves renal recovery, as well as decreasing the risk of progression to chronic kidney disease with fibrosis and consequent permanent renal damage.